Prototype Pengawasan Ruang Server Berbasis IoT dengan Sensor DHT22 dan MQ2 - Haqqi Surya Wicaksono; Iman Saufik Suasana; Dani Sasmoko; Sulartopo Sulartopo; Nuris Dwi Setiawan (Pusat Riset dan Inovasi Nasional, 2026)
Server room security is a critical aspect of industrial operations, including at the Trangkil Sugar Factory, where all digital systems and production machine controls depend on the stability of IT infrastructure. The primary issue often encountered is unstable temperature or extreme humidity, which, if left unaddressed, can damage hardware components or even trigger fire risks due to electrical short circuits. This study aims to design an automated temperature, humidity, and smoke monitoring system based on the Internet of Things (IoT) to minimize these risks. The system was developed using the ESP32 microcontroller integrated with the DHT22 sensor for monitoring temperature and humidity, alongside the MQ2 sensor for smoke detection. The Research and Development (R&D) method was employed to ensure the system's accuracy in a real-world environment. Testing results indicate that the system provides a rapid response; if the temperature exceeds 21°C or humidity goes above 45%, a warning LED is activated. Furthermore, early warnings in the form of real-time notifications are sent directly to the technician's smartphone via a Telegram Bot, and a buzzer is triggered upon smoke detection. With this system, server room supervision becomes more efficient as it can be conducted remotely, allowing potential hardware damage to be prevented at an early stage.